Rel2Doc: Migrating Data from Relational to Document-Oriented Databases - Garbin, Tainam Spagnollo; Duarte, Denio; Schreiner, Geomar A. (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2024: Anais Estendidos do XXXIX Simpósio Brasileiro de Bancos de Dados, 2024)
This paper presents Rel2Doc, a tool to migrate data from relational to document-oriented databases. From normalized concepts, Rel2Doc implements aggregation on the document side using foreign keys and join tables to avoid references in the document-oriented database. We build an interface where the user can choose the relational database source and some parameters to define how primary and foreign keys are implemented on the document-oriented side. Rel2Doc migrates all data regarding correctness and completeness, ensuring that queries have the same answers in both databases.